Application of Bacillus licheniformis γ-glutamyltranspeptidase to the biocatalytic synthesis of γ-glutamyl-phenylalanine. (April 2017) - Chi, Meng-Chun; Lo, Huei-Fen; Lin, Min-Guan; Chen, Yi-Yu; Lin, Long-Liu; Wang, Tzu-Fan
Abstract: Several γ-glutamyl compounds are known to have attractive features for food industry applications. In this study, we report a straightforward procedure for the biocatalytic synthesis of γ-glutamyl-phenylalanine (γ-Glu-Phe) using recombinant Bacillus licheniformis γ-glutamyltranspeptidase ( Bl GGT). The qualitative analysis of reaction products was carried out by thin-layer chromatography technique and computer-assisted image analysis. The optimized conditions for the biocatalytic process were pH 9.0, 50 °C, l -glutamine and l -phenylalanine in a 1:1 ratio, and Bl GGT at a working concentration of 2.0 U/ml. Preparative synthesis of γ-Glu-Phe was also performed at mmol scale. The desired product from the reaction mixture was then verified by mass spectrometry/nuclear magnetic resonance analyses. Strikingly, the experimental results suggest the high potentiality of Bl GGT-catalyzed reaction in the enzymatic synthesis of γ-glutamyl peptides.